2021
DOI: 10.1007/s42452-021-04770-7
|View full text |Cite
|
Sign up to set email alerts
|

Seismic ground response by twin lined tunnels with different cross sections

Abstract: In this paper, the geometrical effects of shallow twin lined tunnels with different cross sections are investigated to obtain the anti-plane seismic ground motion under vertical/horizontal incident plane SH waves. A model of long two-dimensional lined tunnels is established and embedded in a homogeneous linear elastic half-plane by an applied numerical time-domain boundary element approach. In addition to a brief introduction to the formulation of the method, by considering five tunnel sections including circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…In researching the destruction of initial support structures in soft rock tunnels under high ground stress and large deformations, methods commonly used include theoretical analysis [9,10], numerical simulations [11], and field experiments [12,13]. Numerical simulations often employ finite difference methods [14], finite element analysis [11], and boundary element methods [15][16][17][18]. Scholars both domestically and internationally have found through theoretical analysis, numerical simulations, and field tests that the occurrence of large deformations in weak surrounding rock under high ground stress is directly related to geological conditions, original rock stress, and tunnel support methods.…”
Section: Introductionmentioning
confidence: 99%
“…In researching the destruction of initial support structures in soft rock tunnels under high ground stress and large deformations, methods commonly used include theoretical analysis [9,10], numerical simulations [11], and field experiments [12,13]. Numerical simulations often employ finite difference methods [14], finite element analysis [11], and boundary element methods [15][16][17][18]. Scholars both domestically and internationally have found through theoretical analysis, numerical simulations, and field tests that the occurrence of large deformations in weak surrounding rock under high ground stress is directly related to geological conditions, original rock stress, and tunnel support methods.…”
Section: Introductionmentioning
confidence: 99%
“…They confirmed that cavities significantly influenced ground motion at high frequencies. In this context, many researchers have explored the cavity or tunnel effect on seismic ground response under body waves through various methods, such as analytical methods [8][9][10], numerical simulations [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], and model tests [27][28][29][30]. Due to the complexity involved in wave propagation and limitations in modeling complicated systems of equations, numerical techniques are more effective compared to analytical and model tests for the parametric study of ground vibration problems [31].…”
Section: Introductionmentioning
confidence: 99%
“…At present, relevant scholars have carried out a large number of dynamic response studies on the lining section form, tunnel depth, geological conditions, and other working conditions. Mehdi Panji et al [10] found that the enlargement of the horseshoe-shaped tunnel and the square tunnel is the largest. Concerning the buried depth of the tunnel, Jiang et al [11] proposed that the reasonable buried depth of the tunnel in the high-intensity seismic area should be no less than 50 m as far as possible according to the seismic acceleration response of mountain tunnels with different buried depths.…”
Section: Introductionmentioning
confidence: 99%